Combination of MRI‐Guided High‐Intensity Focused Ultrasound and Bioluminescent Biological Systems to Assess Thermal Therapies for Tumor and Tumor Microenvironment. Issue 7 (24th January 2022) - Jeanjean, Pauline; El Hamrani, Dounia; Genevois, Coralie; Quesson, Bruno; Couillaud, Franck
Abstract: This work presents an integrated technology for assessing in vivo anticancer treatments in mice, based on various heating conditions. Bioluminescence imaging (BLI) is used to assess the physiological response of tumor and tumor microenvironment (TME) to heat treatment induced by magnetic resonance‐guided high‐intensity focused ultrasound (MRgHIFU). Transgenic tumor cells and mouse models with either constitutive or thermo‐induced luciferase expressions are combined to monitor cell viability and heat‐induced processes in the tumor and TME. BLI performed after MRgHIFU heating shows that a moderate increase in temperature (45 °C) over 5 min can be exploited to promote heat‐activable treatments in the tumor and its TME, without inducing direct cell death. A higher temperature rise over a shorter exposure time can induce cell death in the tumor, as revealed by a reduction in the BLI signal after treatment. Under these conditions, BLI also reveals that the TME can be stimulated by heat without inducing necrosis. These integrated technologies and models are useful to assess, in vivo in mice, the efficacy of various anticancer strategies exploiting local heat deposition by noninvasive MRgHIFU, including those combining tumor ablation with local drug administration using thermosensitive nanovehicles. Abstract : An integrated technology is presented for assessing in vivo anti‐cancer thermotherapies induced by MRI guided high intensity focused ultrasound. The physiological response of tumor and its microenvironment (TME) to controlled heating conditions is assessed by bioluminescence imaging. This integrated technology allows assessing in vivo, efficacy of anticancer strategies exploiting local heat deposition to combine tumor ablation with TME activation.